Analysis of Leadership Style, Discipline, and Work Motivation on Work Achievement of Aromatique Art Lab Employees - Ramadani, Riky; Hasibuan, Hasrul Azwar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to evaluate the impact of leadership style, work discipline, and work motivation on employee work performance at the Art Aromatique Lab. Data was collected through questionnaires distributed to employees and interviews with superiors. Data analysis was carried out using validity, reliability, classical assumptions, multiple linear regression and hypothesis testing. Research findings reveal that leadership style, work discipline, and work motivation have a positive and significant influence on employee work performance, both partially and simultaneously